Phases of the swim-start in paralympic swimmers are influenced by severity and type of disability - Dingley, A. A.; Pyne, D. B.; Burkett, B. (Journal of Applied Biomechanics, 2014)
Disabilities in Paralympic swimming could impact a swimmer`s ability to execute an effective swim-start. We examined how swim-start performance differed between severity and type of physical disability. Swim-starts were measured in 55 elite Paralympic swimmers from eight different Paralympic classes; S14, S13, S10-S6, S3 grouped as no- (classes S13 & S14), low- (S9 & S10), mid- (S7 & S8) or high- (=< S6) severity of physical disability and also by type of physical disability (upper, lower, and palsy) to provide meaningful comparisons. The swimmer`s competitive level was determined by the international point score (IPS). Swimmers with no physical disability were significantly faster in most swim-start phases compared with those with physical disabilities, as were swimmers with low-severity disabilities compared with the mid- and high-severity groups. Block velocity was highly negatively correlated (r = -0.57 to -0.86) with 15-m swimming time for all groups except high-severity disabilities. Free-swim velocity is a priority area for improving swim-starts for swimmers regardless of disability, given large correlations between this measure and IPS. Swimmers with lower body or high-severity disabilities spent a smaller percentage of time overall in the underwater phase. Assessment of four specific phases of the swim-start highlight distinctive priorities for coaches working with Paralympic swimmers in an applied biomechanical manner.